Script concordance testing in genetic counseling training: A pilot study. - Begun, Yakira S.; Stange, Lila R.; Davis, Claire R. (Journal of Genetic Counseling, 2023)
Clinical reasoning is a complex skill that represents a trainee's ability to use their professional knowledge and skills to assess and solve the problems that arise in clinical practice. As an integral tenet of the genetic counseling process, clinical reasoning skills underlie many of the Practice‐Based Competencies (2019) across a variety of domains. Despite the long‐lasting recognition of the importance of this complex skill in the training of genetic counselors, clinical reasoning has traditionally been difficult to assess in a standardized way in healthcare education. Script concordance testing is a standardized method of assessing clinical reasoning skills in ambiguous clinical situations. The tool has been used to successfully measure the clinical reasoning skills of trainees in various healthcare training programs and has never been used in a genetic counseling training program. We conducted a pilot study to assess the utility of script concordance testing in the field of genetic counseling as an objective measure of clinical reasoning in trainees. The script concordance test was constructed for the field of genetic counseling and administered to 22 second year genetic counseling students in the Joan H. Marks Graduate Program in Human Genetics at Sarah Lawrence College. Twelve genetic counselors served on a panel to provide expert clinical reasoning responses and a scoring grid was developed using the aggregate scores method. The utility of the tool was measured using Cronbach's alpha coefficient, and scores of students and the panel were compared using Hedge's g. Results revealed statistically significant differences between the scores of panelists and students and good reliability. This study shows that script concordance testing can be used to measure clinical reasoning skills in genetic counseling trainees in a way that is reliable, standardized, and easy to use, thereby allowing programs to better assess the clinical reasoning skills of trainees prior to graduation.